Effects of growth regulators on the quality of tomato fruits - Ah. A. Suliman; A. G. Abramov; A. A. Shalamova (Овощи России)
Relevance and methods. This study aimed to improve fruit set and plant performance to increase tomato productivity by studying the effect of plant growth regulators on tomato plants. A specific experiment has been carried out to study the effect of plant growth regulators Hemo bles active substances (850 g/kg) Humic Acid with applied doses (250, 500 and 700 ppm) and Magictone active substances (5-12.5 g/kg) naphthalene acetic acid and naphthalene acetamide with applied doses (250, 500 and 700 ppm) on growth and physiological characteristics of tomato plants (Big Beef F1). The experimental design was a Complete Randomized Blocks Design. Both Hemo bles and Magictone were applied three times (spraying on plants at 30 DAP, spraying on plants at 60 DAP and spraying on plants 90 DAP).Results. The obtained results showed that, Applying Humic Acid “Ener-850” had the highest significant fruit weight (137 g) during the two seasons. Also using “Magictone” had the highest significant Flowers number (48.1), Fruits Number (35.1), Flower Clusters number in the plant (13.6) and Fruits Number (54.6. while (Humic Acid) improved tomato fruit’s quality during improve Dry weight (75.1 g) of Arial parts, Ascorbic Acid, level of Vitamin C and Carotenoids contents (4.82 mg 100 g-1). The results were analyzed using one-way analysis of variance (ANOVA) followed by Tukey’s HSD test with α = 0.05 with the help of MINITAB (v. 19.0) program.